2015
DOI: 10.4028/www.scientific.net/amr.1084.572
|View full text |Cite
|
Sign up to set email alerts
|

Polimer Gafchromic EBT3 Films in Clinical Dosimetry

Abstract: The results of the calibration of the Gafchromic EBT3 polymer film for photon and electron beams with different energies are presented. The results of these studies show that the use of film dosimetry for electron and photon beams in the dose range 0.2 - 40 Gy is possible. The resulting calibration curves are the same for electrons with different energies (2 MeV, 10 MeV), but there exists a difference for photons with the energy of 10 MV and 70 kV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 6 publications
1
4
0
Order By: Relevance
“…However, there is a significant difference for photons with 70 kV and 10 MV energies. The obtained calibrations qualitatively agree with manufacturer's specifications, suggesting that EBT3 films can be used to measure doses within a range of 0.2-40 Gy [18]. On the other hand, Massillon et al [19] showed that EBT3 film is energy-independent at doses above 100 cGy and energies greater than 100 keV photons, making it useful for 192 Ir source, which average photon energy is 380 keV.…”
Section: Table 2 Results Of Gamma Analysis Of the Uncut Filmsupporting
confidence: 71%
See 3 more Smart Citations
“…However, there is a significant difference for photons with 70 kV and 10 MV energies. The obtained calibrations qualitatively agree with manufacturer's specifications, suggesting that EBT3 films can be used to measure doses within a range of 0.2-40 Gy [18]. On the other hand, Massillon et al [19] showed that EBT3 film is energy-independent at doses above 100 cGy and energies greater than 100 keV photons, making it useful for 192 Ir source, which average photon energy is 380 keV.…”
Section: Table 2 Results Of Gamma Analysis Of the Uncut Filmsupporting
confidence: 71%
“…The doses were measured with a 3D-printed applicator that closely followed the doses calculated with a commercial applicator. The results of gamma function tests using the objective test criteria of 3%/3 mm were higher than 94% [18].…”
Section: Table 2 Results Of Gamma Analysis Of the Uncut Filmmentioning
confidence: 74%
See 2 more Smart Citations
“…In an experiment conducted by Sukhikh et al . [ 13 ], the characteristics of one batch of Gafchromic EBT3 polymer film for 10 MeV and 2 MeV electron beams, and 10 MV and 70 kV photon beams were investigated. The obtained relationships showed that the film response was the same in terms of uncertainty for electrons with energies of 2 MeV and 10 MeV, but there was a significant difference for photons with energies of 70 kV and 10 MV.…”
Section: Discussionmentioning
confidence: 99%